Screening for In Vitro and In Vivo Antitumor Activities of the Mushroom Agaricus Blazei - Ziliotto, Liane [UNESP]; Pinheiro, Fabriciano [UNESP]; Barbisan, Luis Fernando [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP] (Lawrence Erlbaum Assoc Inc-taylor & Francis, 2009)
We have investigated the in vitro antitumor activity of the mushroom Agaricus blazei Murill on human cancer cell lines as well as its potential anticancer activity in a model of rat colon carcinogenesis. The in vitro anticancer analysis was performed using 9 human cancer cell lines incubated with organic and aqueous extracts of A. blazei. Antitumor activity was observed with the dichloromethane/methanol and hexanic extracts of A. blazei at 250 g/ml for all cancer cell lines tested. No antiproliferative/cytotoxic activities were detected for the aqueous, methanol, ethyl acetate, or n-butanolic extracts. In the in vivo analysis, crude A. blazei was given orally after carcinogen treatment in a rat medium-term study (20 weeks) of colon carcinogenesis using aberrant crypt foci (ACF) as biomarker. Male Wistar rats were given dimethylhydrazine (DMH) and then were fed A. blazei at 5% in the diet until Week 20. ACF were scored for number and crypt multiplicity. A. blazei intake did not suppress ACF development or crypt multiplicity induced by DMH. No differences in tumor incidence in the colon were observed among the DMH-treated groups. Our results indicate that employing A. blazei in the diet does not have a suppressive effect on colon carcinogenesis.